INTEGRATING OF THE RELIGIOUS AND SCIENTIFIC UNDERSTANDING DURING THE COVID-19 PANDEMIC - Asmawati Asmawati (Al'Adalah, 2022)
This article analyzes the Indonesian people's scientific and religious understanding during the Covid-19 pandemic. It is a crucial topic to discuss because some religious people in Indonesia resist the government policies restricting worship. Based on the analysis, the results obtained include an excessive understanding of religion that will make people increasingly distrustful of reality, so they avoid the scientific explanation. The article also explains that religion is the primary factor in building community perspectives in Indonesia. Nevertheless, science and religion have contributed and should be integrated to solve the problems during the Covid-19 pandemic.